Clinical challenges and technological breakthroughs in helminthic therapy for diabetes - Zhu, Yunhuan; Fei, Xinyi; Wang, Ruke; Wang, Jiyuan; Li, Xianwei; Zhang, Yijie; Xu, Jialu; Zhao, Qingzhi; Chen, Keda; Zhang, Xiaofen; Li, Hongyu (Frontiers in Immunology, 2025)
Helminthic therapy, as an emerging strategy for Diabetes Mellitus (DM), demonstrates significant clinical benefits by modulating host immune and metabolic systems. Studies have shown that this approach effectively enhances insulin sensitivity, reduces chronic inflammation, and restores metabolic homeostasis through the regulation of gut microbiota. However, certain diabetic patients undergoing helminthic therapy may encounter risks such as infections or metabolic disturbances, necessitating the development of safer and more precise therapeutic methods. This review, conducted following the PRISMA guidelines, systematically retrieved and analyzed 163 high-quality studies from PubMed, Web of Science, and Scopus databases. It comprehensively evaluates the mechanisms, clinical outcomes, and safety improvement strategies associated with helminthic therapy. To ensure the safe application of this treatment, we propose strategies including genetic editing, real-time monitoring, targeted therapeutics, and helminth-derived molecules, along with a detailed clinical decision-making framework. This framework encompasses the matching of host health status with helminth species selection, guidance on dose optimization and treatment duration, and the application of modern intelligent technologies for real-time monitoring of therapeutic processes and potential adverse effects. Helminthic therapy has demonstrated success in alleviating hyperglycemia, chronic inflammation, and insulin resistance in diabetic patients, offering substantial health benefits through its immunomodulatory and metabolic regulatory effects. These findings suggest that helminthic therapy holds the potential to become a revolutionary approach in the field of DM.